Techniques to Investigate Neuronal Mitochondrial Function and its Pharmacological Modulation - Jorge M A Oliveira (2011)
Mitochondria are central regulators of neuronal homeostasis and survival, and increasingly viewed as a drug target in several acute and chronic neurological disorders, e. g. stroke, Alzheimer's, Parkinson's, and Huntington's diseases. Frequent working hypotheses aim to establish whether and how chemical or genetic lesions affect mitochondrial function in neurons, and whether this can be rescued by pharmacological treatments. However, the generic designation 'mitochondrial function' actually encompasses a wide spectrum of individual activities, too numerous to be fully quantified by any single available technique. This review aims to provide a broad perspective on the roles played by neuronal mitochondria, and addresses multiple techniques that can be used to derive instructive functional indicators. These include measurements of mitochondrial respiration, ATP production, membrane potential, calcium handling, biogenesis, dynamic movement as well as fusion and fission. Technique descriptions are preceded by a summary of mitochondrial physiology and pharmacological tools required for functional modulation and parameter determination. Hopefully, these will assist researchers interested in testing mitochondria as a drug target in neurological disease models.